Current trends of consanguineous marriages and its association with socio-demographic variables in Pakistan - Khan, Fouzia Zahid Ali; Mazhar, Syeda Batool (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: A high proportion of marriages in South and Middle East Asia are contracted between close biological relatives due to cultural preference as it is a deeply rooted social fashion among these societies. The aim of this study was to determine the frequency of consanguineous marriages and ascertain their relationship to relevant sociodemographic variables. Methods: This was a cross sectional descriptive study conducted in tertiary care hospital of Islamabad. Data were collected on a specially designed questionnaire form. Age of participants, their education, socioeconomic status, castes and number of anomalous children born to these participants, degree of consanguinity and reasons of preferences were inquired. Results: Out of 300 women chosen by convenience sampling technique, 62% had consanguineous marriages, and 38% had a non-consanguineous union. The mean age of women presenting to maternal and child health centre was 27 years. The average age of a woman having consanguineous marriage was 21 years in contrast to 24 years for non-consanguineous nuptial. About 18% of women in consanguineous marriages were illiterate as compared to 5.4% (p = 0.001) of women in non-consanguineous unions. First cousin marriages were more common among certain castes like Rajput and Awan. None in the consanguineous group had any anomalous baby in contrast to non-consanguineous who had two anomalous children (p = 0.0001). There was no significant association between type of marriage and the number of miscarriages (p=0.69). Conclusions: Majority women still prefer cousin unions for their progeny due to traditions and family security reasons irrespective of their education and social status. Therefore, it is important to incorporate prenatal genetic counseling sessions in community programs to raise awareness about repercussions of consanguinity on future generations.